European strategy for vaccine development against infectious diseases. (20th January 2017) - Matthiessen, Line; Lång, Hannu; Klimathianaki, Maria; Hanrahan, Finnian; Kerstiëns, Barbara; Martini, Alessandra; Draghia-Akli, Ruxandra
Abstract: Immunisation efforts save millions of lives every year, but vaccines hold the potential to deliver even greater health benefits for mankind. Vaccine research and development is highly complex, and it requires concerted public funding efforts to support. In this paper we discuss EU funding priorities and the resulting recent advancements in European vaccine research, and we lay out the EU strategy for aiding promising vaccine candidates to successfully reach the market.